Enhanced Effluent Quality of Anaerobic Baffled Reactor (ABR) With Ozone and Aerobic Activated Sludge for Livestock Wastewater Treatment - I Wayan Koko Suryawan; Anshah Silmi Afifah; Muhammad Rizki Apritama; Yosef Adicita; Iva Yenis Septiariva (EPI International Journal of Engineering, 2020)
ABR used to treat wastewater with high COD level such as livestock wastewater. ABR treatment consists of compartments which are limited by vertical bulkhead growth with attached bacteria. However, ABR treatment only capable degraded COD level by 50 – 53%. This value did not qualify to be discharged into the environment. Therefore, ABR treatment need further treatment with ozone treatment and aerobic activated sludge. There were two treatments in this study, which are ABR with ozone treatment and aerobic activated sludge (S1) and ABR with aerobic activated sludge (S2). COD degradation with ozone treatment showed low efficiency, 31.1 ± 1.5 % but BOD/COD level increased. Aerobic activated sludge with batch system showed efficiency of COD degradation as 95.3 ± 2.2 % (with ozone treatment) and 78.6 ± 4.5 % without ozone treatment. The final concentration effluent for livestock wastewater was 167.7 ± 62 mg/L. Aerobic activated sludge with continuous system was conducted to test that result and it average efficiency only decreased into 85%. This concentration was qualified to be discharged into environment.